NGO Resilience: Sustaining Education in Underprivileged Primary Schools Amidst the COVID-19 Pandemic in Bangladesh - Obaidullah, Sharif (Journal of Education Review Provision, 2023)
During the outbreak of COVID-19, all schools and universities in Bangladesh as well as around the globe were closed. For this reason, a large proportion of the disadvantaged students absented themselves from school. This study aims to gain insight into the actual state of underprivileged primary schools in Dhaka that are run by NGOs. Fundamentally, the study looked at how schools are adapting to change and what methods they are using for students interested in continuing their education. Results from qualitative research such as in-depth interviews with participants and FGDs are presented. According to the study, although they were forced to temporarily turn away from their education because of the pandemic, children in underprivileged institutions persevered with their schooling. The pandemic overall brought a massive hurdle to daily life, but people have gotten used to it. It seemed that when the schools closed low-income children would be hard hit. In reality, however, it wasn't nearly as bad as people feared. The study's findings would be extremely useful for gaining a deeper comprehension of the schools' initiatives and motivations amidst the pandemic.